Processos de Curadoria do Museu de Arte Moderna de São Paulo - Colares, Ana Cecília Pamplona Bedê (2010)
This thesis aims to investigate the process of curatorship at the Museum of Modern Art of São Paulo (MAM) and young curators who work at the museum and independently. Understanding the processes of MAMcurator means to approach processes curator of institutions and professionals in Brazil. This work aims to identify processes in the field of practice and theory, and identify histories construction of curatorial activities. This process analysis is done from the readings of the books Gesto inacabado–processos de criação artísticaand Redes da criação –construção da obra de arteof Cecília Almeida Salles. The author brings the basis of Crítica Genética (Genetic Criticism), where the critic looks the artwork done as regards Salles, but follows the creative process. The Crítica Genética (Genetic Criticism) use the route creation to take it apart and then put it into action again. The work is seen through the gesture and work. These ideas were applied heretaking the MAM as a focus, that can generate reflections on the idea of curatorsheep